Effects of dihydromyricetin on ARPE‐19 cell migration through regulating matrix metalloproteinase‐2 expression. Issue 12 (26th September 2018) - Wang, Kai; Yang, Shun‐Fa; Hsieh, Yi‐Hsien; Chang, Yuan‐Yen; Yu, Nuo‐Yi; Lin, Hui‐Wen; Lin, Hung‐Yu
Abstract: Dihydromyricetin (DHM), a flavanonol compound in Ampelopsis grossedentata, possesses several biological activities. However, the molecular mechanism underlying the effects of DHM on human proliferative vitreoretinopathy (PVR) remains unclear. We explored the effects of DHM on cell migration and the metastasis‐promoting proteins in human retinal pigment epithelial (RPE) cells (ARPE‐19 cells). Our results revealed that DHM attenuated ARPE‐19 cell invasion and migration by reducing matrix metalloproteinase‐2 (MMP‐2) expression. Furthermore, a Western blot analysis revealed that DHM significantly reduced levels of phosphorylated c‐Jun N ‐terminal kinase 1/2, but not those of extracellular signal‐regulated kinase 1/2 and p38. In conclusion, our findings shown that DHM inhibits human RPE cell migration through the inhibition of MMP‐2 expression; therefore, DHM may have potential therapeutic value in treating PVR as adjuvant therapy.